(untitled) (World Bulletin of Social Sciences, 2023)
Three articles analyze the marine chronotope created by Irish writer James Joyce and Tokhtamurod Rustam. The article specifically studies the problem of chronotope in the novel "The Adventures of Ulysses" and "The Game of Butterflies". The chronotopes of the novel, the commonalities in the composition and style of the plot, as well as the specific features are highlighted